Fatigue and daytime sleepiness rating scales in myotonic dystrophy: a study of reliability. Issue 10 (16th September 2005) - Laberge, L; Gagnon, C; Jean, S; Mathieu, J
Abstract : Objectives: To assess the reliability of the Epworth Sleepiness Scale (ESS), Daytime Sleepiness Scale (DSS), Chalder Fatigue Scale (CFS), and Krupp's Fatigue Severity Scale (KFSS) in patients with myotonic dystrophy type 1 (DM1). Methods: In total, 27 patients with DM1 were administered the questionnaires on two occasions, with a 2 week interval. Internal consistency and test retest reliability were measured using intraclass correlation coefficients (ICCs), and Cronbach's α, Cohen's κ, and Goodman-Kruskal's γ coefficients. Results: Internal consistency of the CFS and KFSS were adequate (α>0.70) but that of the ESS was weak (α = 0.24). Both daytime sleepiness and fatigue rating scales showed significant test retest reliability. Test retest reliability for individual items revealed inconsistencies for some ESS and CFS items. Conclusions: Reliability of the CFS, DSS, and KFSS was high, allowing their use for individual patients with DM1, but that of the ESS was lower, rendering its current usage in DM1 questionable. Fatigue rating scales such as the KFSS, which are based on the behavioural consequences of fatigue, may constitute a more accurate and comprehensive measure of fatigue severity in the DM1 population.